Routine Immunization Uptake During the COVID-19 Pandemic: A Cross- Sectional Study at an Urban Health Training Centre in Sangli District (Indian Journal of Public Health Research & Development, 2023)
Background: The COVID-19 pandemic has strained the health systems, resulting in around 25 million childrenmissing out on immunization in the year 2021 globally with a sustained drop since 2020. Our study aimed toestimate the proportions of delayed and missed routine immunization with respect to the COVID-19 pandemic,among beneficiaries at an Urban Health Training Centre (UHTC) in Sangli district.Methodology: A cross-sectional observational study was conducted at the immunization clinic of a UHTC in Sanglidistrict, among beneficiaries that availed services of routine immunization & six-monthly vitamin A dose duringthe month of October 2022 at the center. Study participants were enrolled following predefined inclusion andexclusion criteria. Data on the complete vaccination status of each participant was collected from the vaccinationcards and details of delayed & missed immunization were analyzed and statistical tests applied.Results: 548 beneficiaries were included in the study. Among them, 196 beneficiaries had at least one vaccine dose thatwas missed and 295 of them had at least one vaccine that was delayed. 352 of them, i.e. 64% of the study participantsreceived all age-appropriate vaccination. There was a statistically significant increase in delayed immunizationduring the COVID-19 pandemic from 32% to 60% & missed immunization increased from 11% to 43%.Conclusion: Immunization services have been disrupted severely during the pandemic, putting children at riskfor vaccine-preventable diseases. Disrupted vaccination peaked during the peak of the pandemic. There is anurgent need to intensify efforts for catch-up vaccination to address backsliding on routine immunization.
Keywords: Routine immunization, vaccine, COVID-19 pandemic, missed immunization, delayed immunization.